2002
DOI: 10.1080/0141192022000019080
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Schooling on Gender Differences

Abstract: The study on which this article is based examined the gender differences in educational achievements based on a longitudinal sample of more than 45,000 secondary school students in Hong Kong who took a public examination in 1997. The results coincided with the findings from recent British studies that boys did less well than girls in all areas of the school curriculum. The multilevel analyses of the effects of schooling, after controlling for initial ability, indicated that schooling did have an effect on gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 29 publications
2
41
0
5
Order By: Relevance
“…Single-sex schooling may be a reasonable policy response to the underperformance of boys, but to implement such massive changes to any educational system without empirically-based assessments of the consequences of such changes is shortsighted. For example, recent research by Wong et al (2002) on Hong Kong schools found that girls do better in single-sex classrooms while boys do better in mixed-sex classrooms. Other research shows that the performance of both boys and girls improves when the proportion of female students in the classroom increases (Hoxby 2000;Lavy & Schlosser 2007).…”
Section: Data From New Longitudinal Surveys Such As the Ecls-b Ecls-mentioning
confidence: 99%
“…Single-sex schooling may be a reasonable policy response to the underperformance of boys, but to implement such massive changes to any educational system without empirically-based assessments of the consequences of such changes is shortsighted. For example, recent research by Wong et al (2002) on Hong Kong schools found that girls do better in single-sex classrooms while boys do better in mixed-sex classrooms. Other research shows that the performance of both boys and girls improves when the proportion of female students in the classroom increases (Hoxby 2000;Lavy & Schlosser 2007).…”
Section: Data From New Longitudinal Surveys Such As the Ecls-b Ecls-mentioning
confidence: 99%
“…A lot of researchers (Grant & Rong, 1999;Wong, Lam, & Ho, 2002) attempted to explain that gender differences play an essential role in L2 academic achievement. Not only the social context but also gender, as an individual factor, determines significant difference in failure or success in learning of an L2 (Catalán, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In many countries, it is true throughout primary, secondary school, and even in college years (e.g., Epstein, Elwood, Jey, & Maw, 1998;Mau & Lynn, 2001;Perkins, Kleiner, Roey, & Brown, 2004;Pomerantz, Alterman, & Saxon, 2002;Van Houtte, 2004;Willingham & Cole, 1997;Wong, Lam, & Ho, 2002). Although women are still underrepresented in science and mathematics (Ceci, Williams, & Barnett, 2009), they compose nearly 60% of the university student populations in many developed countries (Johnson, 2008).…”
Section: Introductionmentioning
confidence: 99%